Perhitungan Beban Statik pada Rangka Mesin Pengering Padi Menggunakan Baja AISI 1020 - Iwan Nugraha Gusniar; Aqsal Sheva Putra (Jurnal Teknik Mesin, 2021)
In 2007 the government has targeted rice production to reach 61 million tons of dry milled grain (GKG) through the National Rice Production Improvement Program (P2BN). To support this program, it is not only about inputs in the form of area and types of plants cultivated, but also about the need for agricultural tools and machines as supporting factors for farming. The role of mechanization engineering and technology is one of the efforts to create a better and more efficient agricultural system, which includes the provision of machinery and equipment, encouraging farmers to increase land productivity, overcoming transport problems and improving the quality of land and agricultural products. The development of mechanization technology based on physical and socio-economic conditions will have a positive impact on change and encourage the development of agricultural businesses.